1984
DOI: 10.1029/ja089ia12p10903
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal variability of annual changes in activity of equatorial spread F and plasma bubbles

Abstract: Global distribution maps of equatorial spread F (ESF) activity for various annual periods were derived from the topside soundings by the Ionosphere Sounding Satellite b (ISS-b) in 1978-1980. The ESF activity during the northern winter period reveals maximum enhancement at the Atlantic longitudes of large westward geomagnetic declination, and during the northern summer at the Pacific longitudes of large eastward declination. On several orbits passing over the region of the ESF activity enhancement, abrupt deple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
210
2
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(235 citation statements)
references
References 33 publications
21
210
2
2
Order By: Relevance
“…If the transequatorial wind persists for several hours after sunset, a significant lowering of the F layer may occur, which initiates a rapid recombination of the F layer. This argument was used by Maruyama and Matuura [1984] to suggest that the transequatorial wind could be a stabilizing mechanism due to the lowering of the F region in the upwind hemisphere. We have not seen such an effect, but at the same time we acknowledge the lack of completeness in the Northern Hemisphere portion of our TEC distributions.…”
Section: Discussionmentioning
confidence: 99%
“…If the transequatorial wind persists for several hours after sunset, a significant lowering of the F layer may occur, which initiates a rapid recombination of the F layer. This argument was used by Maruyama and Matuura [1984] to suggest that the transequatorial wind could be a stabilizing mechanism due to the lowering of the F region in the upwind hemisphere. We have not seen such an effect, but at the same time we acknowledge the lack of completeness in the Northern Hemisphere portion of our TEC distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Maruyama and Matuura (1984) proposed that the asymmetry in the electron density distribution, which is caused by the meridional winds, could suppress the ESF activity. However, they did not show the seasonal variation in the asymmetry in the density distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Now, it is known that there are some candidate mechanisms helping the ESF development. These are (1) the pre-reversal enhancement (PRE) in upward E×B drift and associated uplifting of the F-layer (Fejer et al, 1999;Whalen, 2002), (2) a small or null transequatorial component of the thermospheric winds and associated symmetry in the equatorial ionization anomaly (EIA) (Maruyama and Matuura, 1984;Maruyama, 1988;Mendillo et al, 2000Mendillo et al, , 2001, (3) a simultaneous decay of the E region conductivity at both ends of the field line (Tsunoda, 1985;Stephan et al, 2002), and (4) a sharp gradient at the bottomside of the F-layer (Kelley, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies on the occurrence characteristics of ionospheric density irregularities using groundbased measurements (Rastogi, 1980;Abdu, 2001), satellitebased in situ measurements (Watanabe and Oya, 1986;Huang et al, 2002;Burke et al, 2004), and topside sounders (Maruyama and Matuura, 1984), and many important features of these have been reported including temporal variations (Sahai et al, 2000;Huang et al, 2002), seasonallongitudinal variability (Burke et al, 2004), several-day variation, and day-to-day variation (Basu et al, 1996) though several enigmatic features of them are yet to be revealed (Thampi et al, 2009). However, studies on continuous and global characteristic features of ionospheric plasma irregularities are very scanty due to the fact that the global coverage is difficult to obtain from ground-based observations.…”
Section: Introductionmentioning
confidence: 99%